In Vitro Evaluation of Antibacterial Activity from Nephelium lappaceum L. Leaf Ethanolic Extract and Fraction against Some Foodborne Pathogens - Imam Adi Wicaksono; Raden Bayu Indradi; Danni Ramdhani; Resmi Mustarichie (Journal of Global Pharma Technology, 2020)
Fooborne pathogens are causing foodborne illness with significant effects on human health. Some of the most common foodborne bacteria that cause foodborne illness are Bacillus cereus and Shigella dysenteriae. Nephelium lappaceum L. is known to have antibacterial potential because of these plants have secondary metabolites such as flavonoid and polyphenols. The ethanolic extract and fractions of Nephelium lappaceum L. was investigated for antibacterial activities including determine of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against foodborne pathogens. The extraction of N. lappaceum L. was done by maceration method with 70% ethanol and fractionationed by liquid-liquid extraction to obtain ethyl acetate, water, and n-hexane fractions. Secondary metabolite content and profile determination of N. lappaceum L. was done by phytochemical screening and thin layer chromatography. The antibacterial activities were determined using the agar diffusion method, MIC and MBC value determined by dilution method using the test tube. The results showed that the ethanolic extract, ethyl acetate fraction and water fraction of N. lappaceum L. had antibacterial activity against Bacillus cereus isolate and Shigella dysenteriae bacteria. The value of MIC and MBC of the extract in the concentration range between 0.08%(w/v) – 0.15%(w/v) against B. cereus isolate and 2.5%(w/v) – 5%(w/v) against S. dysenteriae, which the ethyl acetate fraction in concentration range between 0.04%(w/v) - 0.08%(w/v) against B. cereus isolate and 1.25%(w/v) – 2.50%(w/v) against S. dysenteriae bacteria. The ethyl acetate fraction is the most active fraction because it had the best activity, MIC and MBC values when compared to the results against both of test bacteria.